Perancangan UI/UX untuk Pendaftaran Data Calon Karyawan dengan Metode User Centered Design pada PT Pra Kerja Nusantara - Rafiq, Muhammad Nur; Wibowo, Edi (LPPM STT Terpadu Nurul Fikri, 2025)
This study discusses the design of User Interface (UI) and User Experience (UX) for the website-based job applicant registration process using the User-Centered Design (UCD) method. PT Pra Kerja Nusantara previously used paper forms to fill in applicant data manually. Now, the company is switching to a website-based system to improve efficiency and effectiveness, but it needs to be optimized to make it easier to use. This research focuses on designing a website for job applicant registration at PT Pra Kerja Nusantara by considering user needs through the UCD method. The design process involves problem analysis, user research, system design, high-fidelity prototyping, and testing and evaluation. The results showed a prototype job applicant registration website with a System Usability Scale (SUS) score of 90.71, indicating an excellent usability level. With the application of effective UI/UX, this website is expected to help PT Pra Kerja Nusantara process and store data efficiently and effectively.